Coach carter - Carter, Thomas (Madrid Paramount Home Entertainment, 2004)
Controversy surrounds high school basketball coach Ken Carter after he benches his entire team for breaking their academic contract with him
Writers: Mark Schwahn, John Gatins
Audio: Inglés y castellano. Subt.: Inglés y castellano
Samuel L. Jackson, Rick Gonzalez, Robert Ri'chard
No apta para menores de 7 años
Keywords: Películas cinematográficas -- DVD